Application of Sandplay Therapy in the Mental Health Education of Vocational College Students. (29th June 2022) - Xu, Xiaojing; Zhang, Yanhua; Liu, Libin
Abstract : Objective . To analyze the application and effect of sandplay therapy in higher vocational students' mental health. Method . 350 sophomores of 2019 in a higher vocational college were randomly selected, and 72 subjects of depressed students (SAS ≥ 50 ) were selected from 350 sophomores and randomly divided into the intervention group and the control group, each group 9, preparing one set of chamber equipment, adopting the same group before and after test experiment design. The intervention group was, respectively, given 8 individual box court game tutoring, once a week for each person. The control group did not intervene. By comparing the intervention group with the control group, the intervention effect of sandplay therapy on anxiety of experimental group members was investigated. Results . Among 350 respondents, 72 had SAS scores ≥ 50, and the incidence of anxiety symptoms was 20.57%. Since there was only 1 case with SAS score ≥ 70, it was incorporated into the group with SAS score ranging from 60 to 59. After treatment, SAS scores of students with mild to moderate anxiety in the intervention group decreased, and the difference was statistically significant. The difference before and after control group was not statistically significant. After sandplay therapy, the differences in SAS scores between the intervention group and the control group were found to be statistically significant for both mild and moderate anxiety. Conclusion . Sandplay therapy in the higher vocational college students' mental health education could promote the mental health of students, and it effectively improves students' psychological quality.